Classroom management and its impact on the teaching learning process with the students of 1st, 2nd and 3rd years of high school curriculum at “Pio Jaramillo Alvarado” high school, morning section, academic year 2009 - 2010 - CELI CELI, LILIANA FERNANDA (2011)
The researches show off this worked named: “CLASSROOM MANAGEMENT AND ITS IMPACT ON THE TEACHING LEARNING PROCESS AMONG THE STUDENTS OF 1ST, 2ND AND 3RD YEARS OF HIGH SCHOOL CURRICULUM AT “PIO JARAMILLO ALVARADO”. ACADEMIC YEAR 2009 – 2010. MORNING SECTION”, whose general objective is “to determine how the teacher’s leadership influences on the students’ learning process among the students of 1st, 2nd and 3rd years of High School Curriculum at “Pio Jaramillo Alvarado” High School, morning section. Academic Period 2009-2010. To accomplish this research we took advantage of the scientific, analytical-synthetic, explicative, inductive-deductive methods. To collect the key information we made use of the surveys which were directed to teachers and students. As hypothesis the research group set up two: “The teacher does not consider the Classroom Management styles into the students’ learning on the Teaching Learning Process” and “The class is interrupted by the students with their disruptive activities, affecting in this way the Teaching Learning Process” at “Pio Jaramillo Alvarado” High School. Both were proved according to the got results and the respective analysis made by the researches. Most of students said that there is not a constant arrangement of the classroom. They work every day in the same environment. They are aware of the benefits that this important issue has, and the most important fact, they would like to work in a better atmosphere. Teachers confirmed that the class is always disrupted by the students with frequently tardiness, gums, cellphones, chit chat and so on. Even though, establishing school rules is a demanding task that requires much effort by both parts, as students as teachers, affirmed that it is a kind of hard to fulfill all the rules which were established at the beginning of the class.